NECESIDAD DE INCORPORAR LOS ASUNTOS DE CAMINOS EN EL CÓDIGO ORGÁNICO DE LA FUNCIÓN JUDICIAL - Quevedo Chamba, Andrés Anselmo (2016)
The Constitution of the Republic of Ecuador as the supreme law, Title VII Scheme of good living, Inclusion and Equity Chapter One, EI national social inclusion and equity is the cohesive and coordinated systems, institutions, policies, standards, programs and services that ensure the performance, security and enforcement of the rights recognized in the Constitution and the fulfillment of the objectives of the scheme of development, and there are also related laws such as the Law of Civil Organic Judiciary Applicative to Regulation Roads Act, Civil Code, Code of Civil Procedure, speaking on the matter of jurisdiction unit processes roads. These laws are created with the purpose of regulating the management of public and private roads, the same should be based on jurisdictional unity and rule under the principles of competence and jurisdiction. The unit is being studied jurisdictional competition must have a civil judge in matters of roads. It must be considered that these processes belong to the Civil procedural system, so that they practice the principle of jurisdictional unity in matters of roads, grounds for having selected the theme "need to incorporate ROADS IN MATTERS Organization Code THE JUDICIAL funsion ", because I believe that it should reform the competence of a civil judge in matters of roads, because within the detailed study that has been done to the above laws I have seen, people are harmed not to apply the jurisdictional unity, the memento to request the opening or closing of a road. This research work contains relevant topics such as the origin and definition of paths, concepts and definitions and rural roads in Ecuador, the path from the legal standpoint, the traditional ways as road infrastructure, and then make a law firm with such topics as legal analysis to competition on road has been awarded to a dependent Administrative Officer Ministry of Public Works, attentive the principle of jurisdictional unity and its treatment should be incorporated into 5 the Organic Law of the Judicial , forming the central motif of this research work. The research I have done decamp by guest 9 questions by technical survey of lawyers in free exercise law, Carrera professors of law, as well as interviews of seven questions to MOP officials and civil judges, allowing the testing of the hypothesis targets. Once the field investigation, proceeded to tabulate the results for later analysis and interpretation by the same set of conclusions and recommendations, as well as reform pres pawning. Thus concluding my research work, which I believe will provide scientific input for future research of both students, teachers and the general public.